Research on optimization methods for large-flow coefficient centrifugal compressors - Yang, Changzhu; Fan, Liyun; Chen, Shuo; Zhang, Hanwen; Wu, Yuelin (Frontiers in Energy Research, 2024)
The present paper focuses on the optimization of large-flow coefficient centrifugal compressors, utilizing a mature centrifugal compressor impeller with a flow coefficient of 0.16 under design point condition in engineering as the research subject. Due to the more complex flow mechanism and more design parameters in the impeller with large flow coefficient, the traditional artificial optimization method is insufficient. In present paper, the impeller with a large flow coefficient is optimized using the concept of combining physical principles and artificial intelligence tools. Firstly, the impeller underwent a redesign based on the theory of maximum flow capacity, with the aim of reducing the Mach number at the impeller inlet to enhance the compressor’s performance. And the efficiency of the impeller at the design point has been increased from 88.6% to 89.9%. In order to further improve the performance of the impeller, an optimization algorithm grounded in gradient variation was employed to facilitate the automatic compressor optimization, and the flow losses at the impeller’s top under low-flow conditions has been mitigated. The results of three-dimensional numerical simulation showed that the operating range of the new impeller is 7% wider than that of the original impeller.